Language and identities in US communities of Italian origin. (August 2014) - De Fina, Anna
In this article I discuss relationships between language use and identity among Italian Americans. I argue that the study of identities needs to abandon essentialist stances that are particularly common in research on Italian Americans, and approach identity construction as a process that takes place within concrete social practices enacted by specific communities. I provide a brief overview of the linguistic development of Italian Americans in the USA in order to provide a frame of reference to the discussion of the links between language use and identities. I then focus in particular on the following phenomena: symbolic uses of individual Italian words or expressions within talk in English, engagement with the heritage language in Italian-American families and storytelling, to illustrate how Italianness is constructed through those practices in different communities. I use these examples also to problematize the idea that knowledge of the heritage language is central to ethnic identification.